(untitled) (@limentech, Ciencia y Tecnología Alimentaria, 2016)
The consumption of fruits and vegetables in the daily diet can prevent chronic non-communicable diseases such as cardiovascular disease, diabetes mellitus, ischemic heart disease, cerebrovascular disease, chronic respiratory tract disease, and cancer, due to their high content of micronutrients, dietary fiber, and bioactive compounds; however, consumption of these foods in Colombia is limited. The objective of this research was to identify the nutritional composition of the leaves of the whistling plant (Geoffroea spinosa Jacq) from the Los Tres farm in the municipality of Tubará (Atlántico). To obtain the samples, the plant was harvested, the leaves were selected, and then washed, dried, and ground. The parameters pH, moisture, ash, fat, protein, crude fiber, carbohydrates, zinc, calcium, iron, and magnesium were determined. The results revealed 6.21 pH, 3.335% humidity, 9.531% ash, 0.639% fat, 20.535% protein, 20.386% crude fiber, 45.575% carbohydrates, 56.53 mg/100 g zinc, 5793.90 mg/100 g calcium, 241.27 mg/100 g iron, 3250.64 mg/100 g magnesium. The leaves of the whistler are an important source of nutrients necessary for human nutrition, constituting an alternative vegetable consumption due to its high content of proteins, carbohydrates, fiber, calcium and magnesium.